Deconstruction of Meaning and Structure in Chairil Anwar's Poetry: Structuralism and Postmodernism Approaches - Ananda, Nadia; Sakina, Fasla (BHASWARA: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Chairil Anwar, a seminal figure in modern Indonesian literature, is renowned for his complex poetic expressions that reflect both personal and socio-political dimensions. His works have been widely studied, yet a comprehensive analysis that juxtaposes structuralist and postmodernist approaches remains limited. This study aims to explore the intrinsic and extrinsic elements of Chairil Anwar's selected poems by applying structuralism to uncover the deep structures and linguistic patterns, and postmodernism to interrogate fragmented meanings, intertextuality, and the poet’s deconstruction of dominant narratives. Using qualitative content analysis, the research examines five representative poems, focusing on narrative structure, stylistic devices, and thematic complexities. The findings reveal that structurally, Anwar’s poetry maintains a coherent internal logic and symbolic consistency, while postmodern reading exposes ambiguities, paradoxes, and resistance to singular interpretations. This dual approach highlights the richness of Anwar’s poetic voice and situates his work within both national literary tradition and broader global discourses. The study concludes that integrating structuralist and postmodernist frameworks provides a more nuanced understanding of Chairil Anwar’s poetry, opening new perspectives for literary criticism in the Indonesian context.